Utilization Of Social Media As A Learning Media For Promoting Sampit Language. Issue 4 (March 2020) - Anggraini, Gita; Ramadhan, Sandy; Fauzi; Permata Sari, Dwi Maulina; Bernianti
Abstract: Nowadays, social media not only functions as a medium for self-promotion and socializing. The emergence of many social media-based learning platforms opens up opportunities for the development of learning media. Social media is liked by all groups, easily accessible and inexpensive to become its strength, so it is very strategic if used as a learning medium. Sampit language itself is a language that is owned by one of the Dayak tribes in Central Kalimantan. Some facts on the ground show that the existence of the Sampit language is currently under threat. Through the use of social media as learning media, the Sampit language has begun to be looked at again by young people. Social media used as learning media here are Instagram and YouTube channel and learning material that is packaged in the form of videos and images. The research aimed at knowing the utilization of social media for promoting social media.The type of research used in this study is quantitative descriptive research, with data collection methods using questionnaires and observations. The results of this study indicate that the use of social media can increase the popularity of the Sampit language.